Peran Unit Kegiatan Mahasiswa dalam Mengembangkan Minat dan Bakat Mahasiswa di Universitas Muhamadiyah Buton - Zainal Abidin; Anwar Sadat; Muh Askal Basir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
The purpose of this study was to determine the Role of the Student Activity Unit in Developing the Interests and Talents of Muhammadiyah Buton University Students. The type of research used in this research is descriptive research with a qualitative approach. Data collection techniques namely Observation, Interview, Documentation and Literature Study. Data analysis techniques in research are data reduction, data presentation, and drawing conclusions. The results obtained in this study are the role of UKM as a forum for students to develop their interests and talents, because students can make UKM as a place to study and develop their abilities, Student Activity Units can develop students' creativity and critical thinking, because students are used to solving work programs giving rise to creativity. and students' critical thinking. In fulfilling the interests and welfare of UKM UM Buton students, they must maximize the fulfillment of the basic needs of members. Maximizing the development and actualization of members. Optimizing family-based activities in order to strengthen relationships between members